Physical and Chemical Characterization of Fuel Ethanol Coproducts Relevant to Value-Added Uses - Muthukumarappan, K.; Rosentrater, Kurt A.; Bhadra, Rumela (My University, 2010)
One of the fastest growing industries in the United States is the fuel ethanol industry. In terms of ethanol production capability, the industry has grown by more than 600% since the year 2000. The major coproducts from corn-based ethanol include distillers dried grains with solubles (DDGS) and carbon dioxide. DDGS is used as a livestock feed because it contains high quantities of protein, fiber, amino acids, and other nutrients. The goal of this study was to quantify various chemical and physical properties of DDGS, distillers wet grains (DWG), and distillers dried grain (DDG) from several plants in South Dakota. Chemical properties of the DDGS included crude ash (5.0–21.93%), neutral detergent fiber (NDF) (26.32–43.50%), acid detergent fiber (ADF) (10.82–20.05%), crude fiber (CF) (8.14–12.82%), crude protein (27.4–31.7%), crude fat (7.4–11.6%), and total starch (9.19–14.04%). Physical properties of the DDGS included moisture content (3.54–8.21%), Aw (0.42–0.53), bulk density (467.7–509.38 kg/m³), thermal conductivity (0.05–0.07 W/m•°C), thermal diffusivity (0.1–0.17 mm²/sec), color L* (36.56–50.17), a* (5.2–10.79), b* (12.53–23.36), and angle of repose (25.7–47.04°). These properties were also determined for DWG and DDG. We also conducted image analysis and size determination of the DDGS particles. Carbon group characterization in the DDGS and DDG samples were determined using NMR spectroscopy; O-alkyl comprised >50% of all DDGS samples. Results from this study showed several possibilities for using DDGS in applications other than animal feed. Possibilities include harvesting residual sugars, producing additional ethanol, producing value-added compounds, using as food-grade additives, or even using as inert fillers for biocomposites.
Keywords: Fuel ethanol coproducts; Physical properties; Chemical properties; Distillers dried grains with solubles (DDGS); Distillers wet grains (DWG); Distillers dried grain (DDG); Value-added uses